Cancer Treatments Using Low-Temperature Plasma - Tanaka, Hiromasa; Mizuno, Masaaki; Ishikawa, Kenji; Toyokuni, Shinya; Kajiyama, Hiroaki; Kikkawa, Fumitaka; Hori, Masaru (Current Medicinal Chemistry, 2021)
Low-temperature plasma (LTP) is a partially ionized gas that contains electrons, ions, radicals, light, etc. Recently, the bio-medical application of LTP has become a hot topic in plasma science and biological science. Cancer treatment with plasma is the most challenging topic in plasma bio-medical applications. Many in vitro and in vivo experiments have been conducted to investigate the anti-tumor effects of LTP. Extracellular reactive oxygen and nitrogen species (RONS) in plasma-activated solutions are key factors for the anti-tumor effects, and amino acid modifications by LTP may affect cellular responses. Intracellular RONS are also key factors for the anti-tumor effects. Various signaling pathways, such as p53 signaling pathways, survival and proliferation signaling pathways, and oxidative stress-dependent signaling pathways are activated by LTP.
Keywords: plasma cancer therapy